ASGHAR ALI ENGINEER DAN REFORMULASI MAKNA TAUHID - Muhaemin Latif (Prodi Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Filsafat UIN Alauddin Makassar, 2018)
This paper examines the notion of Asghar Ali Engineer’s view on tauhid. Engineer is one of the leading thinkers as well as an activist who was not only generating the ideas of rethinking but also involved in a variety of activities relating to reformation of Islamic thought. This employs qualitative research through collecting datas and information from different manuscripts, books, and journals. The main objective of this research is demonstrating the urgency of reformulating the meaning of tauhid. The finding suggests that tauhid is the core of Islamic teaching. It is the basic tenet of any religions that may generate a power to liberate human being from any kind of discrimination. In other words, tauhid is an energy that can guide mankind released from ignorance, oppression and poverty. Tauhid not only concerned on the unity of God but also the oneness of society. Classless society is the ultimate goal of tauhid that lead to set the people on the same position before the God.